Studying the Effect of H2SO4/H2O Ratio on the Properties of Positive Electrode in Lead-acid Battery - S. Hussain, Muslet; A.K. Jabbar, Sundos (Iraqi Journal of Chemical and Petroleum Engineering, 2008)
The lead-acid battery has become so dependable in its used applications of automobile starting, emergency lighting and telecommunications, which left an impression that no further investigation is necessary or desirable. While there has been slow continuous improvements in lead-acid battery performance and mainly limited to design and material engineering. This work is mainly devoted to the properties of the active mass of the positive electrode and the acid/water ratio during the manufacturing process. A field study is carried out at the State Battery Manufacturing Company located in Baghdad, to prepare batches of lead mono-oxide with predefined quantities of liquid additives (i.e. sulfuric acid and water). Quality control and laboratory routine analysis using X-ray diffraction, porosimeter and BET techniques, as well as density, penetration tests of residual lead content ware conducted during the batch process. After the assembling of the positive plates produced during this research into the final product, final testing including electrical capacity and dry charging were performed. It was concluded from the results obtained, that the effective H2SO4/H2O ratio and hence H2SO4/PbO ration and paste density with α/β-PbO2, are the limiting factors of the electrical capacity and durability of the batteries concerned.